2017
DOI: 10.3390/s17092104
|View full text |Cite
|
Sign up to set email alerts
|

Leak Detection and Location of Water Pipes Using Vibration Sensors and Modified ML Prefilter

Abstract: This paper proposes a new leak detection and location method based on vibration sensors and generalised cross-correlation techniques. Considering the estimation errors of the power spectral densities (PSDs) and the cross-spectral density (CSD), the proposed method employs a modified maximum-likelihood (ML) prefilter with a regularisation factor. We derive a theoretical variance of the time difference estimation error through summation in the discrete-frequency domain, and find the optimal regularisation factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Previous studies have shown that the vibroacoustics technique can be adopted to locate the leakage in buried pipelines through measurements using acoustic/vibration sensors either installed along the pipeline or on the ground surface due to the dispersion and radiation characteristics of leakage signals [4][5][6][7][8][9][10][11][12][13][14]. Moreover, the principle of interior detection is based on leak noise propagation in a tube: a microphone is mounted within a sphere that runs with the water flowing in the pipe [15]; when the sphere moves to the vicinity of the leakage point, the acoustic signal collected by the sensor will increase rapidly, resulting in larger signal amplitude when the distance between them gets shorter.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the vibroacoustics technique can be adopted to locate the leakage in buried pipelines through measurements using acoustic/vibration sensors either installed along the pipeline or on the ground surface due to the dispersion and radiation characteristics of leakage signals [4][5][6][7][8][9][10][11][12][13][14]. Moreover, the principle of interior detection is based on leak noise propagation in a tube: a microphone is mounted within a sphere that runs with the water flowing in the pipe [15]; when the sphere moves to the vicinity of the leakage point, the acoustic signal collected by the sensor will increase rapidly, resulting in larger signal amplitude when the distance between them gets shorter.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of non-revenue water has been reported to be 15.2-35.1% of drinking water supply in United States (http://nepis.epa.gov/), 6.5-24.6% in Europe (http://www.ndew.de/), and 4.3-27.0% in Korea (http://me.go.kr/). These losses can be classified into unbilled public usage, apparent losses which include unauthorized consumption and metering inaccuracies, and real losses through overflows at storage tanks and burst leaks in distribution pipelines which were caused by bad connections, pipe corrosion, and physical damages (Choi et al, 2017). Therefore, early detection of leakage in water pipeline is of great importance to reduce water production costs and to protect the safety of public (Puust et al, 2010;Ishido and Takahashi, 2014;Martini et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Among all the leak detection methods, the most popular approach for water leakage is to install acoustic/vibration sensors or pressure transducers (Choi et al, 2017). With the utilization of two sensors, the leak can be located by estimating the time difference through correlation of the signals received.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the limited pipe length coverage and higher cost are the limiting factors for the broad acceptance of this method. Relatively common method of leak detection is to sense the vibration or sound wave emanating from the leak location [3] [4]. However, these methods of leak detection are highly dependent on the 1 44685K13 part number from McMaster process parameters such as pipe diameter, material, medium and noise from the pump and traffic nearby [5].…”
Section: Introductionmentioning
confidence: 99%